2008
DOI: 10.1111/j.1439-0396.2007.00731.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oregano (O. majorana × O. vulgare) on performance and antioxidative capacity of quails fed a diet rich in ω3 fatty acids

Abstract: Oregano possesses high antioxidant activity and could therefore be used to enhance oxidative stability of eggs high in omega3 fatty acids. In this study, 20 female quails were fed a diet containing 4% linseed oil. They were divided into two groups, one receiving oregano, and the other grass meal as control (2% respectively). Cholesterol oxidation products were analysed in fresh eggs, in stored eggs and in the livers. Trolox equivalent antioxidative capacity of plasma was measured. No significant differences we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 12 publications
(14 reference statements)
1
12
0
Order By: Relevance
“…In view of the published data on the antimicrobial efficacy of essential oil (EO), the following general ranking (in order of decreasing antibacterial activity) can be made: oregano / clove / coriander / cinnamon > thyme > mint > rosemary > mustard > cilantro / sage (Sara, 2004). Recent studies have also shown that OEO is effective as antioxidant and flavoring agent with the properties of functional food or nutraceutical products , retarding lipid oxidation (Handl et al, 2008); which makes oregano a source of EO with potentially extensive use in the food industry.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the published data on the antimicrobial efficacy of essential oil (EO), the following general ranking (in order of decreasing antibacterial activity) can be made: oregano / clove / coriander / cinnamon > thyme > mint > rosemary > mustard > cilantro / sage (Sara, 2004). Recent studies have also shown that OEO is effective as antioxidant and flavoring agent with the properties of functional food or nutraceutical products , retarding lipid oxidation (Handl et al, 2008); which makes oregano a source of EO with potentially extensive use in the food industry.…”
Section: Introductionmentioning
confidence: 99%
“…First is the increase of serum glycosylated protein, which is a parameter caused by glucose and other reducing sugars such as ribose and fructose reacting with the amino residues of proteins to form Amadori products, for instance, glycosylated hemoglobin (HbA 1c ) and the O 2 − are also generated in the process of AGE formation. OM could directly decrease the formation of glycated hemoglobin, possibly as a result of its antioxidative activity [69]. …”
Section: Discussionmentioning
confidence: 99%
“…Among the herbs of the Lamiaceae family, rosemary has been more extensively studied and its extracts are the first marketed natural antioxidants. Majorana which belongs to the same family, has gained the interest of many research groups as a potent antioxidant [69]. …”
Section: Introductionmentioning
confidence: 99%
“…Hammad et al (1996) did not observe any effect of a diet supplementation with 0.5% crystalline cholesterol on the cholesterol content of the yolk of quails. Sahin et al (2004) demonstrated that dietary supplementation with chromium and biotin in quails prevented the cholesterol increase in yolk induced by heat distress; however, Handl et al (2008) observed no effect of oregano (O. majorana 9 O. vulgare) on oxidative stability of eggs high in omega 3 fatty acids. Yalc ßin et al (2009) tested an inclusion of dried baker's yeast on the diet of laying quails and concluded that it can be used up to 16% in their diet without adverse effects on blood serum levels of cholesterol.…”
Section: Introductionmentioning
confidence: 99%
“…() demonstrated that dietary supplementation with chromium and biotin in quails prevented the cholesterol increase in yolk induced by heat distress; however, Handl et al. () observed no effect of oregano ( O. majorana × O. vulgare ) on oxidative stability of eggs high in omega 3 fatty acids. Yalçin et al.…”
Section: Introductionmentioning
confidence: 99%